Calculation of the Van der Waals Potential of Argon Dimer Using a Modified Tang-Toennies Model (Journal of Atomic and Molecular Sciences, 2011)
The Tang-Toennies (TT) potential model was modified based on the physical nature of the interatomic interaction to describe the $Ar-Ar$ potential very accurately in the short range of the repulsive region. Using the modified TT potential model, the ground state van der Waals potential energy curve of $Ar_2$ was calculated. Compare to the experimental result, the current potential shows that the modified potential model not only gives the precise result in the long-range part, but also gives quite accurate result in the short-range repulsive part.
Keywords: modified TT potential model; argon dimer; van der Waals potential.